EKSPLORASI GERAK AIR DALAM VISUALISASI FOTOGRAFI STILL LIFE - Prasetyo, Andry (Acintya, 2015)
The research on the art work entitled â€œEksplorasi Gerak Air Dalam Visualisasi Fotografi Still Lifeâ€Â (The Exploration of Water Movement in Photography Visualization Still Lifeâ€ aims to create aÂ photography work with the object of water spot that quickly moves and forms a certain pattern thatÂ cannot be caught by eyes, that is then paused so that it can be enjoyed in detail by high speedtechnique. The research uses experimental approach. It is executed through two stages covering analysisÂ and development. The analysis includes identification and studies on the research object includingÂ water movement or water spot and the material forming a certain pattern as an object ofÂ photography. The method of photography creating Still Life covers three stages: exploration,Â planning, and realization. The result shows that firstly, the beauty of the photograph Still Life with theÂ object of water spot can be caught and seen by eyes with high speed technique. Secondly, the imageÂ of water movement that is freezed can produces visual element and aesthetic effect by adding the lightÂ of lamp in the background at the time the photograph is taken.Keywords: photography Still Life, water movement, exploration.